PEMANFAATAN FUNGI Aspergillus flavus, Aspergillus terreus, DAN Trichoderma harzianum UNTUK MENINGKATKAN PERTUMBUHAN BIBIT Ceriops tagal - Devita Mala Sari; Yunasfi Yunasfi; Budi Utomo (Peronema Forestry Science Journal, 2015)
Deteriorating of mangrove cause many impacts it deteriorate happen because too many land clearing activities in mangrove for harber, public building, and fishponds. Dergadation of mangrove should immediately resolved, one of them is with rehabilitation in mangrove areas use fungi which are expected to increase growth of plants and can be survive. The research was conducted from June 2014 until January 2015 using Completely Randomized design (CRD). There are 3 types of fungi treatment with five replications. Fungi that use are  A.flavus, A.terreus, and T.harzianum. Application of T. harzianum gave the best result on seedling growth of Ceriops tagal spesies with an average height is 2.68 cm, a diameter is 0,226 cm, leaf area is 89.89 cm2, and total dry weight is 4.02 g. They are  compared with control seeds and the provision of other fungi.   Keywords: Ceriops tagal, fungi, rehabilitation, seedling.